From astronauts to stroke survivors: how the TheraSuit Method® can boost balance and recovery - Lampert, Rose; Goel, Rahul; Oblanca, João V.; Martins, Daniel F. (Frontiers in Neurology, 2025)
The human body exhibits remarkable adaptability to diverse environments. Astronauts in microgravity experience physiological changes like those observed in stroke patients due to inactivity. This shared challenge inspires the exploration of rehabilitation methods, bridging the gap between space medicine and physical therapy. This perspective examines the physiological similarities between microgravity and stroke, focusing on proprioceptive deficits. We then introduce the axial loading suit astronauts use to counteract these deficits and its potential application in stroke rehabilitation. We propose the TheraSuit Method®, a suit utilizing similar principles, as a promising tool to enhance whole-body proprioception and facilitate muscle activation against gravity, thereby promoting strength and functional recovery in stroke patients.